7-(-5d)=52

Simple and best practice solution for 7-(-5d)=52 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7-(-5d)=52 equation:



7-(-5d)=52
We move all terms to the left:
7-(-5d)-(52)=0
We add all the numbers together, and all the variables
-(-5d)-45=0
We get rid of parentheses
5d-45=0
We move all terms containing d to the left, all other terms to the right
5d=45
d=45/5
d=9

See similar equations:

| -6x+1=4x-39 | | 5−-5d=52 | | -98=-84+12s | | 6x+4=-3x+76 | | 10=4j+2 | | 19-3f=4 | | 0.05*x-0.6=7.85 | | -6.2-1.4x=-0.7x-3 | | 134=-5x=4(6x+5) | | 16e-23=-4e-5-e | | 2=-1+x/8 | | 10=z/4+7 | | Y=x+3Y=1/4x | | y-18=96 | | -7=-2x+5(-x+14) | | 4=3s−2 | | y=(-1)-7 | | x*0.05-0.6=7.85 | | 2x+66=3x | | y=2/3(-3)+4 | | x=28+5/7 | | 41=-6+5w | | 6x-5(-4x-12)=-174 | | 6x=25=79 | | y-13=97 | | 720=28x-84 | | 7=p-23 | | 8x-4+3x+17+17x-23=180 | | -150=-2x-3(6x-10) | | 38=4x-4 | | -150=-2x-3(6x-10 | | 12345678000000=u |

Equations solver categories